Simmons Longitudinal Study: Adaptation and Development Across the Lifespan (New England, United States), Age 21 Data, Wave 6, 1993-1994 - Reinherz, Helen Z. ([Verlag nicht ermittelbar], 2009)
The Simmons Longitudinal Study (SLS) is a community-based study that has prospectively traced the life course of a single-aged cohort from childhood (age 5) to adulthood (age 26). Data were collected from multiple informants at seven major time points: age 5 (1977), age 6 (1978), age 9 (1980-1981), age 15 (1987), age 18 (1990), age 21 (1993-1994), and age 26 (1998). Since its inception in 1977, the SLS has utilized a multidisciplinary, multimethod approach, with the dual goals of: (1) tracing the development and course of academic difficulties, behavior problems, and psychopathology; and (2) identifying factors that promote health functioning from early childhood (age 5) to adulthood (age 26). The SLS has consistently emphasized the identification of modifiable social and environmental risk and protective factors that can be targeted directly in prevention and intervention programs. To date, SLS has published 50 journal articles and 9 book chapters. The original study group was comprised of every child who entered kindergarten in the fall of 1977 in one public school district in a northeastern town in the United States. For this wave of the study, Wave 6, researchers spoke with respondents, then 21 years old in 1993, and their mothers or other close family member. This early-adulthood period was a varied developmental stage for the group: some respondents were away from home attending college, others were married and working full-time, and a number were living with their parents as they pursued their education and career paths. Similar to the age-18 data wave, diagnostic information on a variety of mental health problems was collected. In addition, the interviews focused on current education and career activities; family, peer, and romantic relationships; and other aspects of current behavioral and emotional functioning.